The New quality productive forces empower Beijing’s red publishing - Wang, Chutong; Zhou, Wei (International Theory and Practice in Humanities and Social Sciences, 2025)
This article will delve into the profound impact of new productive forces on the innovation and development of red publications in the Beijing area. The article will elaborate on how red publications carry rich party history culture and revolutionary spirit, as well as the diverse forms they present. As a treasure trove of red publication resources, Beijing not only possesses a vast amount of historical documents and materials but also has a wide audience for its red publications, including young students, history enthusiasts, and middle-aged and elderly groups. These publications perform well in the market, with their influence continuously growing. The application of new productive forces in the field of red publications is extremely extensive, for example, the emergence of digital publishing platforms enables red publications to achieve more efficient dissemination and provide more personalized services. In addition, the application of various advanced technologies, such as Augmented Reality and Virtual Reality , greatly enhances the reading experience, making red cultural education more vivid and appealing. The integrated marketing strategy of social media and new media matrices has also effectively enhanced the dissemination effect and market penetration of red publications. Looking to the future, red publications in the Beijing area are expected to continue innovating in various aspects such as technological innovation, content creativity, and market expansion.